Acciones educativas de enfermería para el control de la esteatosis hepática no alcohólica - María Fernanda, Cutiupala Ponce (2020)
Nonalcoholic hepatic steatosis (NAHS) is a clinical-pathological condition characterized by excessive accumulation of fat in the liver in the absence of secondary causes and constitutes the frequent etiology of chronic liver disease without proven effective therapy, in most patients this happens in cases such as obesity, metabolic syndrome and sedentary lifestyle, associated with alterations in flora and intestinal permeability. This research work aims to determine the educational nursing actions aimed at the control of non-alcoholic hepatic steatosis. A bibliographic review is carried out, by searching for both: national and international papers from pages such as Medigraphic, Scielo, Elsevier, Pubmed. After the investigation and with the respective analysis of several articles and authors, it was concluded that the role of nursing is fundamental, especially because it is required to modify the lifestyle of these users through education, on adequate physical activity and consumption of a balanced diet, actions that play a key role in order to avoid complications and other chronic pathologies, in the same way, it will participate by providing adequate knowledge to patients about their disease, as well as conducting active listening and promoting self-efficacy so that the patient feels well with himself or herself.